2004
DOI: 10.1038/sj.bjc.6602278
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the tumoral expression of β3-integrin and outcome in cervical cancer patients who had undergone radiotherapy

Abstract: Integrins are cell-surface receptors, which mediate cell-to-cell and cell-to-extracellular matrix adhesion. Besides playing an important role in tumour angiogenesis, b3-integrin is also expressed in several types of epithelial cancer cells. It was the purpose of the present study to evaluate the prognostic value of b3-integrin expression in patients with cervical cancer. Biopsies were taken from 82 patients with squamous cell or adenocarcinomas of the uterine cervix who had undergone external-beam radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Certain integrins are typically expressed at only low levels in normal epithelial cells, but show high levels in some tumors. For example, avb3 expression is associated with disease progression and metastasis in melanoma (Nip et al 1992;Danen et al 1994) and pancreatic (Hosotani et al 2002), prostate (McCabe et al 2007), breast (Felding-Habermann et al 2001), ovarian (Landen et al 2008), and cervical (Gruber et al 2005) cancers.…”
Section: Integrin Signaling Promotes Diverse Functions In Multiple Tumentioning
confidence: 99%
“…Certain integrins are typically expressed at only low levels in normal epithelial cells, but show high levels in some tumors. For example, avb3 expression is associated with disease progression and metastasis in melanoma (Nip et al 1992;Danen et al 1994) and pancreatic (Hosotani et al 2002), prostate (McCabe et al 2007), breast (Felding-Habermann et al 2001), ovarian (Landen et al 2008), and cervical (Gruber et al 2005) cancers.…”
Section: Integrin Signaling Promotes Diverse Functions In Multiple Tumentioning
confidence: 99%
“…Interestingly, avh3 integrin also binds to ECM components fibronectin and osteopontin, which along with vitronectin, are highly expressed in bone marrow. Although the expression of this integrin is normally associated with leukocytes and osteoclasts (36,38,39), it is up-regulated in several malignancies of epithelial origin, including those of the breast, lung, and cervix, as well as glioblastoma and melanoma (36,38,40,41).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments using a murine model of bone metastatic prostate cancer in which tumor cells express either wild-type, mutant, or no avh3 integrin expression show its requirement for tumor formation in the bone matrix (44). It is also important in the metastasis of breast and lung cancer to the bone marrow (41), and is associated with metastasis and decreased progression-free survival in cervical cancer (40).…”
Section: Introductionmentioning
confidence: 99%
“…These integrins seem to be involved in the control of the radiation resistance of other tumor types. Indeed, it was shown that expression of the β3 integrin was correlated with survival without progression and overall survival after irradiation in patients treated for cervix carcinoma [17]. Pharmacological inhibition of the pathways of these integrins also led to radiation sensitization of non-small cell lung carcinoma [18].…”
Section: Rationalementioning
confidence: 98%